2018
DOI: 10.1111/eva.12724
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization rate and hybrid fitness for Camelina microcarpa Andrz. ex DC (♀) and Camelina sativa (L.) Crantz(Brassicaceae) (♂)

Abstract: Hybridization between crops and their wild relatives has the potential to introduce novel variation into wild populations. Camelina ( Camelina sativa ) is a promising oilseed and cultivars with modified seed characteristics and herbicide resistance are in development, prompting a need to evaluate the potential for novel trait introgression into weedy relatives. Little‐podded false flax (littlepod ; Camelina microcarpa ) is a naturalized weed in Canada and the USA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
0
24
0
2
Order By: Relevance
“…However, little is known about the process of domestication in this taxon, although future population genetic studies in C. microcarpa may elucidate the demographic history of C. sativa. Hybrid formation between C. microcarpa and C. sativa has been observed (Séguin-Swartz et al, 2013;Martin et al, 2018) and may prove to be a valuable tool in generating novel cultivars of C. sativa with drought tolerance, disease resistance, and earlier flowering.…”
Section: Descending Dysploidies In Camelina Were Mediated By Unusually Complex Chromosomal Rearrangementsmentioning
confidence: 99%
“…However, little is known about the process of domestication in this taxon, although future population genetic studies in C. microcarpa may elucidate the demographic history of C. sativa. Hybrid formation between C. microcarpa and C. sativa has been observed (Séguin-Swartz et al, 2013;Martin et al, 2018) and may prove to be a valuable tool in generating novel cultivars of C. sativa with drought tolerance, disease resistance, and earlier flowering.…”
Section: Descending Dysploidies In Camelina Were Mediated By Unusually Complex Chromosomal Rearrangementsmentioning
confidence: 99%
“…The collections of C. microcarpa species in different genebanks suggest that it has a diverse range of origin including the Mediterranean region, Armenia (Brock et al 2018), Germany, Poland, Czechia, Slovakia andGeorgia (Martin et al 2017;Smejkal 1971). Diversity studies, analyses of genome size and chromosome number along with the success of hybridization efforts between C. microcarpa and C. sativa (Séguin-Swartz et al 2013;Martin et al 2019) suggested the close relationship between these two species (Brock et al 2018;Martin et al 2017). However, not all the results were so encouraging with varying levels of hybridization success depending on the genotype (Séguin-Swartz et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ex DC [ 16 , 17 ]. With similar genome sizes and well-documented interfertility [ 18 , 19 ], crosses between C. microcarpa and C. sativa could increase genetic diversity in the crop and introduce traits for agronomic improvement. Camelina microcarpa has been estimated to harbor roughly twice the genetic diversity of C. sativa [ 17 ], which further suggests that this wild species could be valuable for breeding programs.…”
Section: Introductionmentioning
confidence: 99%